Book Review - Handbook of Research on K-12 Online and Blended Learning - Mayse, Diane Lynn (Online Learning, 2015)
The Handbook of Research on K-12 Online and Blended Learning, which is edited by Richard E. Ferdig and Kathryn Kennedy, is designed to be a collection of what is currently known about research in the field of K-12 online and blended learning and to serve as a resource for researchers, practitioners, and policy makers. Richard Ferdig is an accomplished researcher and current professor of Learning and Instructional Technologies at Kent State University. His research, teaching, and service work focus on combining cutting-edge technologies with current pedagogic theory to create innovative learning environments, such as educational games and simulations. Ferdig is also the editor-in-chief of the International Journal of Gaming and Computer Mediated Simulations and the associate editor-in-chief of the Journal of Technology and Teacher Education. He currently serves as a consulting editor for the development editorial board of Educational Technology Research and Development and on the review panel of the British Journal of Educational Technology. Kathryn Kennedy is an award-winning teacher, researcher, and professor in the area of curriculum and instruction with a focus on educational technology. Kennedy is a senior researcher at the Michigan Virtual Learning Research Institute (MVLRI)–an organization with the goals of supporting new learning models, engaging in active research to inform new policies in online and blended learning, and strengthening the infrastructure for sharing best practices. She was awarded the International Association for K-12 Online Learning (iNACOL) Online Learning Innovator Award for Outstanding Research in 2010 and 2012. The intended audience of this book includes anyone working, researching, teaching, or interested in learning more about K-12 online and blended learning. The editors’ purpose was to create a publicly available, free online resource to begin to synthesize the various strands of research in K-12 online and blended learning into one comprehensive catalogue. The editors’ thesis is that this resource will strengthen further research in the K-12 online and blended learning field by clarifying what is currently known and what is currently unknown; provide empirical resources for researchers, educators, administrators, and policy officials; and begin a process of annually reexamining research in the field.